Chondroid lipoma of the right thigh: correlation of imaging findings and histopathology of an unusual benign lesion - Setiawati, Rosy; Dimpudus, Franky; Sun, Zhonghua (Australasian Medical Journal Pty Ltd, 2012)
Chondroid lipoma is a rare and unusual benign soft tissue lesion. Although there have been several reports of the imaging findings of chondroid lipoma, very few described the radiographic calcification or ossification in a chondroid lipoma. We present a case of chondroid lipoma with adipose tissue and ossified components on plain radiography and MRI images. Correlation of imaging findings and pathological examination is provided to confirm the diagnosis.